2020
DOI: 10.1128/mbio.02634-20
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of the Gut Microbiome in Resisting Norovirus Infection as Revealed by a Human Challenge Study

Abstract: Norovirus infections take a heavy toll on worldwide public health. While progress has been made toward understanding host responses to infection, the role of the gut microbiome in determining infection outcome is unknown. Moreover, data are lacking on the nature and duration of the microbiome response to norovirus infection, which has important implications for diagnostics and host recovery. Here, we characterized the gut microbiomes of subjects enrolled in a norovirus challenge study. We analyzed microbiome f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
(104 reference statements)
1
27
0
Order By: Relevance
“…In this way, our CHIM offers the ability to study three potential dysbiosis-inciting events: antibiotic prophylaxis with rifaximin, challenge with C. jejuni , and administration of dual antibiotic treatment with ciprofloxacin and azithromycin. Previous CHIM studies focusing on enterotoxigenic Escherichia coli (ETEC) and norovirus and the human gut using either 16S rRNA gene sequencing or metagenomics exist; however, none have specifically targeted the changes in the human gut microbiome during C. jejuni infection ( Pop et al., 2016 ; Patin et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, our CHIM offers the ability to study three potential dysbiosis-inciting events: antibiotic prophylaxis with rifaximin, challenge with C. jejuni , and administration of dual antibiotic treatment with ciprofloxacin and azithromycin. Previous CHIM studies focusing on enterotoxigenic Escherichia coli (ETEC) and norovirus and the human gut using either 16S rRNA gene sequencing or metagenomics exist; however, none have specifically targeted the changes in the human gut microbiome during C. jejuni infection ( Pop et al., 2016 ; Patin et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Chen et al observed increased Proteobacteria in HuNoV infected children compared with healthy controls [24]. Microbiome analysis of symptomatic and asymptomatic HuNoV-infected patients by 16S rRNA sequencing revealed enrichment in Clostridia (Firmicutes) and depletion of Bacteroidia (Bacteroidetes) in symptomatic individuals compared with asymptomatic individuals [51]. These studies point to alterations in the gut microbiota in response to HuNoV.…”
Section: Norovirus (Family: Caliciviridae Genus: Norovirus)mentioning
confidence: 91%
“…Pigs with highly diverse microbiomes or hosting nonpathogenic E. coli strains have an improved outcome after being infected with the porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) ( 51 ). Patin et al ( 52 ) studied the microbiomes of humans and then challenged them with norovirus. They compared the prechallenge microbiome of people with symptoms of virus infection against that of people without symptoms.…”
Section: Microbiome Mitigation Of Viral Infectionmentioning
confidence: 99%